2018
DOI: 10.1038/s41598-018-34494-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced microbubble contrast agent oscillation following 250 kHz insonation

Abstract: Microbubble contrast agents are widely used in ultrasound imaging and therapy, typically with transmission center frequencies in the MHz range. Currently, an ultrasound center frequency near 250 kHz is proposed for clinical trials in which ultrasound combined with microbubble contrast agents is applied to open the blood brain barrier, since at this low frequency focusing through the human skull to a predetermined location can be performed with reduced distortion and attenuation compared to higher frequencies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 62 publications
4
58
0
Order By: Relevance
“…Images of ~20 single nanoemulsion particles, and ~20 oscillating microbubbles were captured and processed. Microbubble are known to expand with sonication at a center frequency of 250 kHz [34]. Indeed, with microbubbles, we observed an expansion ratio of 35 at a peak negative pressure (PNP) of 500 kPa (Fig.…”
Section: These Nanoemulsions Do Not Undergo Large Oscillations or Cavmentioning
confidence: 79%
“…Images of ~20 single nanoemulsion particles, and ~20 oscillating microbubbles were captured and processed. Microbubble are known to expand with sonication at a center frequency of 250 kHz [34]. Indeed, with microbubbles, we observed an expansion ratio of 35 at a peak negative pressure (PNP) of 500 kPa (Fig.…”
Section: These Nanoemulsions Do Not Undergo Large Oscillations or Cavmentioning
confidence: 79%
“…The experimental setup (illustrated in Fig. 2A) was described previously (55) and further described in SI Appendix. Postprocessing of the captured images was performed in Matlab to yield the resting MB radius and expansion ratio.…”
Section: Methodsmentioning
confidence: 99%
“…In the past, it was assumed that MB oscillations are maximized around their resonance frequency (2 to 10 MHz) (51)(52)(53)(54). Recently, we showed that when MBs are excited by a frequency of 250 kHz (an order of magnitude below the resonance frequency of these agents), their oscillations reach an expansion ratio of 35 at a relatively low PNP of 500 kPa (55). For tumor transfection, we hypothesize that the high-amplitude MB oscillations occurring at a center frequency of 250 kHz will enhance the uptake of the genetic material, allowing for more copies to be delivered and resulting in a higher transfection efficacy.…”
mentioning
confidence: 99%
“…8), respectively. Lower frequencies favor cavitation-mediated bioeffects at low acoustic pressures (Apfel and Holland 1991;Ilovitsh et al 2018). We have shown here that the BBB can be opened in an NHP model at an MI of 0.4 ( Fig.…”
Section: Discussionmentioning
confidence: 56%